Nanostructured magnesium oxide microspheres for efficient carbon dioxide capture. Issue 51 (September 2021) - Chammingkwan, Patchanee; Mai, Le Thi Tuyet; Ikeda, Tomohiro; Mohan, Priyank
Graphical abstract: Highlights: MgO microspheres were synthesized from thermal decomposition of spherical magnesium ethoxide prepared by controlled particle growth method. Successful control of macroparticle morphology offered MgO with high bulk density and flowability. Microscopically, MgO microspheres consisted of nano-sized MgO as building units, resulting in high surface and high pore volume. Due to high surface area and high pore volume, nanostructured MgO microspheres exhibited excellent performance in CO2 sorption. Abstract: A new method to synthesize nanostructured magnesium oxide (MgO) microspheres with high surface area and bulk density was reported based on thermal decomposition of spherical magnesium ethoxide prepared by the controlled particle growth method. Various characterizations, including scanning electron microscopy, transmission electron microscopy, powder X-ray diffraction, attenuated total reflection infrared spectroscopy, and N2 adsorption/desorption, were performed. The results revealed the successful conversion of the precursor into MgO while keeping macroscopic characteristics of the original precursor. Due to the agglomeration of nano-sized MgO as building blocks, the synthesized MgO microspheres possessed a mesoporous structure with tunable surface area (up to 227 m 2 g −1 ) and pore volume (up to 0.791 cm 3 g −1 ). With the high surface area and pore volume, MgO microspheres showed a remarkable performance in carbon dioxide sorption.